A new vascular access route for balloon angioplasty in extremely low birth weight infants. (8th September 2015) - Kanagawa, Nao; Inamura, Noboru; Tominaga, Yuji
Abstract: In this study, we present the case of an extremely low birth weight infant with severe coarctation of the aorta after ductus ligation. We treated the patient with balloon angioplasty using the descending aorta as a new access route. This method reduced many complications typically observed during the intervention for extremely low birth weight infants, which may expand the available treatment options for extremely low birth weight infants.